1994
DOI: 10.1007/bf00578085
|View full text |Cite
|
Sign up to set email alerts
|

Coplanar interdigitated band electrodes for electrosynthesis

Abstract: The behaviour of coplanar cathodic and anodic band electrodes was investigated and their use for standard syntheses was proven to be considerably advantageous, when compared to other techniques. Electrode arrays were fabricated by screen printing platinum, silver or carbon inks. The inter-electrode distances were in the range 1 mm to 250 pm for a constant band width of 1 mm.The mass transport was characterised for different inter-electrode distances and flow conditions. Figures compared positively with other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 13 publications
(1 reference statement)
0
22
0
Order By: Relevance
“…Flow through systems have been proposed with channel geometry [27] or with flow through porous plug electrodes [28]. Rather than employing a flow-through system with anode and cathode placed vis-a`-vis, electrode geometries such as the interdigitated electrode array can be highly effective [29] (see Figure 2a). An interdigitated electrode system (arrays of microscopic electrodes made from metal sputtered into patterns onto a substrate) system can now be produced routinely and in extremely small dimensions via advanced lithographic techniques [30].…”
Section: Pairing Electrosynthetic Processesmentioning
confidence: 99%
“…Flow through systems have been proposed with channel geometry [27] or with flow through porous plug electrodes [28]. Rather than employing a flow-through system with anode and cathode placed vis-a`-vis, electrode geometries such as the interdigitated electrode array can be highly effective [29] (see Figure 2a). An interdigitated electrode system (arrays of microscopic electrodes made from metal sputtered into patterns onto a substrate) system can now be produced routinely and in extremely small dimensions via advanced lithographic techniques [30].…”
Section: Pairing Electrosynthetic Processesmentioning
confidence: 99%
“…The electrode geometry improves the pumping efficiency by reducing the current path through the solution which also serves to lower the heat generation. 119 When current or voltage is applied, with the drug as an electrolyte, electrolysis of water in the drug at the electrodes produces oxygen and hydrogen gases. The gases generated result in an internal pressure increase in the sealed reservoir which causes drug to be released through the cannula and into the eye.…”
Section: A Micro-electromechanical Devicementioning
confidence: 99%
“…In the first part of the investigation, a theoretical analysis showed that a reduction of the cell voltage could be obtained by this approach [3]. In the next step, a theoretical description was verified by furan methoxylation as a model reaction [4], followed by propylene epoxidation as a second example of an electroorganic reaction [5]. Both systems provided results comparable to, or even better than, most efficient industrial cells.…”
Section: Introductionmentioning
confidence: 96%
“…At the time Belmont and Girault [3][4][5][6][7][8] published a series of papers dealing with the utilization of interdigitated band electrodes for electroorganic synthesis. The approach they used overcame the construction problem of obtaining a cell with the electrodes fixed at a submillimeter distance by depositing them at regular distances on a suitable planar substrate.…”
Section: Introductionmentioning
confidence: 99%